Self-Compassion with Loneliness in Late Teens Who Are Migrating - Biring, Reski Natalia; Wibowo, Doddy Hendro (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Late adolescence is a time when individuals begin to prepare themselves to determine their future. For this reason, many teenagers choose to migrate for the sake of their desired future, but late teens often experience loneliness. To reduce feelings of loneliness, teenagers need to increase self compassion for themselves. This research aims to determine the relationship between self compassion and loneliness in late adolescents who are migrating. This study uses a quantitative approach. The number of samples in this study was 203 young people who were currently migrating, sampling using the quota sampling technique. The measuring instrument used in this research is the Self Compassion Scale (SCS). Loneliness scale version 3 (UCLA version 3). The data analysis technique used is the Pearson Product Moment correlation technique. The results of this study show a correlation coefficient of r = -0.510 with a significance value of 0.000 (p<0.01), which means there is a significant negative relationship between self compassion and loneliness in late adolescents who are migrating. This means that the higher the self compassion, the lower the level of loneliness experienced by teenagers who are migrating. Vice versa, the lower self compassion, the higher the level of loneliness experienced by teenagers who are migrating. The implication of this research is that late adolescents who are migrating are not immersed in feelings of loneliness and need to increase self compassion by carrying out activities according to their own desires or are popular which provide benefits for themselves and the people around them, to avoid feelings of loneliness.Masa remaja akhir merupakan masa dimana individu mulai mempersiapkan diri untuk menentukan masa depan. Oleh sebab itu banyak remaja memilih untuk merantau demi masa depan yang diinginkan, namun remaja akhir sering mengalami loneliness. Untuk mengurangi perasaan loneliness maka remaja perlu meningkatkan self compassion pada dirinya. Penelitian ini bertujuan untuk mengetahui hubungan antara self compassion dengan loneliness pada remaja akhir yang sedang merantau. Penelitian ini menggunakan pendekatan kuantitatif. Jumlah sampel dalam penelitian ini sebanyak 203 remaja akhir yang sedang merantau, pengambilan sampel pada menggunakan teknik quota sampling. Alat ukur yang digunakan pada penelitian ini yaitu skala Self-Compassion Scale (SCS). Skala Loneliness scale version 3 (UCLA versi 3). Teknik analisis data yang digunakan yaitu teknik korelasi Product Moment Pearson. Hasil penelitian ini menunjukan koefisien korelasi r = -0.510 dengan nilai signifikansi 0.000 (p<0.01) yang berarti terdapat hubungan negatif signifikan antara self compassion dengan loneliness pada remaja akhir yang sedang merantau. Artinya, semakin tinggi self compassion maka semakin rendah tingkat loneliness yang dimiliki remaja yang sedang merantau. Begitu pun sebaliknya, semakin rendah self compassion maka semakin tinggi tingkat loneliness yang dimiliki remaja yang sedang merantau. Implikasi dari penelitian ini, yaitu remaja akhir yang sedang merantau tidak terlarut dalam perasaan loneliness dan perlu meningkatkan self compassion dengan melakukan aktivitas sesuai dengan keinginan diri sendiri atau digemari yang memberikan manfaat bagi diri sendiri dan orang disekitar, sehingga terhindar dari perasaan loneliness.